The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1090/memo/0844
|View full text |Cite
|
Sign up to set email alerts
|

A geometric mechanism for diffusion in Hamiltonian systems overcoming the large gap problem: heuristics and rigorous verification on a model

Abstract: Chapter 1. Introduction 1 Chapter 2. Heuristic discussion of the mechanism 2.1. Integrable systems, resonances, secondary tori 2.2. Heuristic description of the mechanism Chapter 3. A simple model Chapter 4. Statement of rigorous results Chapter 5. Notation and definitions, resonances Chapter 6. Geometric features of the unperturbed problem Chapter 7. Persistence of the normally hyperbolic invariant manifold and its stable and unstable manifolds 7.1. Explicit calculations of the perturbed invariant manifold Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
452
3
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 136 publications
(461 citation statements)
references
References 66 publications
(130 reference statements)
2
452
3
4
Order By: Relevance
“…In this paper we perform an accurate process of truncation of the Fourier series of the perturbation and we present a deeper study of the geography of resonances. Using this, we are able to extend and simplify some of the results in [DLS06a] and apply them to an a priori unstable Hamiltonian system with a generic perturbation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper we perform an accurate process of truncation of the Fourier series of the perturbation and we present a deeper study of the geography of resonances. Using this, we are able to extend and simplify some of the results in [DLS06a] and apply them to an a priori unstable Hamiltonian system with a generic perturbation.…”
Section: Introductionmentioning
confidence: 99%
“…The goal of this paper is to present a generalization of the geometric mechanism for global instability (popularly known as Arnold diffusion) in a priori unstable Hamiltonian systems introduced in [DLS06a]. That paper developed an argument to prove the existence of global instability in a-priori unstable nearly integrable Hamiltonian systems (the unperturbed Hamiltonian presents hyperbolicity, so that it can not be expressed globally in action-angle variables) and applied it to a model which presented the so called large gap problem.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A system of this type is called a priori unstable. The drift of orbits along the cylinder has been actively studied in the last decade [3][4][5][7][8][9]12,[18][19][20]22,27,28,[31][32][33][34]70,87,88], including the problem of genericity of this phenomenon and instability times. It should be noted that the Arnold diffusion can be much faster in this case.…”
Section: Introductionmentioning
confidence: 99%
“…The process can be described using the notion of a scattering map introduced by Delshams et al [32]. Earlier Moeckel [75] suggested that Arnold diffusion can be modelled by random application of two area-preserving maps on a cylinder (this approach was recently continued in [17,[46][47][48][49]53,66]).…”
Section: Introductionmentioning
confidence: 99%